Development of Eco-Friendly Biocomposite Films Based on Whey Protein Isolate and Carboxymethyl Cellulose with Silica as a Filler - Azwar; Mukhlishien (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This research endeavor focuses on the development of biodegradable composite films. The constituents utilized comprise Whey Protein Isolate (WPI) and Carboxymethyl Cellulose (CMC). Additionally, varying quantities of silica filler are incorporated into the formulations. Films were created using two different CMC amounts (0.75g and 1g) and varying silica levels (0g, 0.05g, 0.15g, 0.25g, 0.35g, and 0.45g). The research systematically examined how the addition of silica affected the films' thickness (which increased from 0.126 mm to 0.371 mm with higher silica content), water absorption, biodegradability, and surface structure. Silica addition also reduced water absorption significantly, improving the film’s resistance to swelling. Biodegradation tests showed all samples met the SNI biodegradability standard (>60%), although higher silica levels reduced the rate of degradation due to its hydrophobic nature. SEM analysis illustrated that films with added silica exhibited smoother, denser surfaces with fewer voids, indicating improved particle distribution and better structural integrity. Overall, the incorporation of silica and CMC successfully enhanced the functional performance of WPI-based biocomposite films. The optimal silica concentration (0.05–0.25 g) provided a good balance between mechanical strength, water resistance, and environmental degradability.